Expert systems within taxation: Competencies for employees - Faina, I.; Alturas, B.; Almeida, F. (2020 15th Iberian Conference on Information Systems and Technologies (CISTI), 2020)
Expert Systems (ES) is increasing its importance, impacting not only personal life but also professional life and its workplace. With ES's growing impact on tax areas, tasks of tax practitioners will change and progress. In addition to financial, legal and tax knowledge, these workers will need to develop and apply technical and analytical knowledge for the use of ES. This research proposal proposes to study the relationship between the presence of ES in taxation and the skills that the labour market imposes. The aim of this study is not only to identify the skills required for technological work within taxation, but also to build and validate a model that contributes to an improvement in the ability to predict workers' ability to adapt to new work demands.